Inovasi Tujuan Kurikulum Pesantren dalam Menjawab Tuntutan Masyarakat Modern - Marpu'ah, Eva; Fauzan, Fauzan; Shidiq, Sapiudin (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study aims to analyze the innovation of curriculum objectives at the al-Hikamussalafiyah Islamic Boarding School in Cipulus, Purwakarta. Innovation of curriculum objectives is an important step in responding to the demands of modern society for education. Al-Hikamussalafiyah Islamic Boarding School is one of the Islamic boarding schools that is able to innovate and transform from traditional learning to more modern learning. The methodology used in this study is a qualitative method with a case study approach. Data were collected through interviews, observations and document studies. The data were then analyzed using the triangulation method. The conclusions of this study are: Innovation of learning objectives at the al-Hikamussalafiyah Islamic Boarding School in Cipulus, Purwakarta is carried out by establishing formal education and teaching non-formal vocational and skills education. This innovation of learning objectives answers several demands of modern society, namely: technology integration, educational gaps, teacher training, mental health and well-being, relevant curriculum, funding and resources, performance measurement and assessment, globalization and diversity, and school security.